2022
DOI: 10.3390/foods11244060
|View full text |Cite
|
Sign up to set email alerts
|

Pasting and Rheological Properties of Starch Paste/Gels in a Sugar-Acid System

Abstract: This study was to investigate the impact of granule size, amylose content, and starch molecular characteristics on pasting and rheological properties of starch paste/gels in neutral (water) and sugar–acid systems. Normal rice starch (RS), waxy rice starch (WRS), normal tapioca starch (TS), and waxy tapioca starch (WTS) representing small-granule starches and intermediate-granule starches respectively, were used in the study. Impacts of granule size, AM content, and their synergistic effects resulted in differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…HY71 and RD12 granules were clearly larger, and their size was more uniform, compared to SMJ and RD6. The large granule size of RD12 compared to those of RD6 and SMJ is likely indicative of their characteristics within their respective cultivars, as our results are consistent with previously reported results [ 5 , 17 ]. There were no reports of granule size of HY71.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…HY71 and RD12 granules were clearly larger, and their size was more uniform, compared to SMJ and RD6. The large granule size of RD12 compared to those of RD6 and SMJ is likely indicative of their characteristics within their respective cultivars, as our results are consistent with previously reported results [ 5 , 17 ]. There were no reports of granule size of HY71.…”
Section: Resultssupporting
confidence: 93%
“…The value of G′ of an 8% native waxy maize starch gel studied by Wang et al [ 10 ] was ~8 Pa, and its tan δ of 0.6 indicated that the material was a soft gel. A 6% WRS gel studied by Boonkor et al [ 17 ] displayed a G′ of ~15 Pa and a tan δ of 0.5. Precha-Atsawanan et al [ 9 ] studied the stiffness of 15% gels from native and debranched WRS, and observed a G′ of 30 Pa for the native starch gel, with a tan δ of 0.3, and a very high G′ of 1000 Pa, with a tan δ of ~0.02 for the debranched starch.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The setback value denotes the anti-retrogradation ability and gelatinization of starch. The smaller the setback value, the better is the anti-retrogradation ability; however, it cannot easily to form gel [45]. The breakdown and setback values of instant rice, reconstituted rice, and instant reconstituted rice were significantly smaller than those of rice; this result indicates that the pasteurization stability of the puffed samples was better, and they could not be easily hardened and undergo retrogradation during cooling.…”
Section: Analysis Of Thermal and Pasting Propertiesmentioning
confidence: 95%